A Comparative Study on Academic Achievement of Mathematics and English with Other Subjects of Secondary Level in BTR of Assam, India, Using Mahalanobis Distance. (29th March 2022) - Ahmed, Eusob Ali; Karim, Mohammad Rezaul; Banerjee, Munmun; Sen, Subir; Chatterjee, Prasanta; Mandal, Gurudas
Abstract : The present work is a comparative study of four different subjects' achievements such as mathematics, English, general sciences, and social studies between two student groups in the Bodoland Territorial Region (BTR) in Assam, India. Three different types of groups are considered viz., tribal and nontribal, boys and girls, and rural and urban from different secondary and higher schools of BTR. Mahalanobis Distance (MD) is used to calculate the difference in dynamical nature of achievement between two groups of students in four subjects. The result revealed that there is no significant difference between boys and girls; students from tribal and nontribal communities, students belonging to the rural and urban schools, tribal boys and nontribal boys, and tribal girls and nontribal girls in the dynamical character of achievement of different groups are taken into account.